MYOCARDIAL INFARCTION AND HEMOPHILIA - A. S. Galyavich; N. Yu. Stekolshchikova; R. A. Kasimova; F. I. Mukhamednazarova (Российский кардиологический журнал)
The rare case of myocardial infarction and hemophilia A is presented. Brief review is provided of this issue by literature data. Accent is done upon the opportunities of myocardial infarction treatment in hemophilia patients.